2016
DOI: 10.1161/circresaha.116.309301
|View full text |Cite
|
Sign up to set email alerts
|

Innate Effector-Memory T-Cell Activation Regulates Post-Thrombotic Vein Wall Inflammation and Thrombus Resolution

Abstract: Deep vein thrombosis (DVT) is the most common type of venous thromboembolism. Patients with DVT are at risk of developing potentially life-threatening complications, such as pulmonary embolism, but also long-term complications, including post-thrombotic syndrome and chronic thromboembolic pulmonary hypertension.1 Current treatments for DVT focus on preventing clot expansion with anticoagulants and vasoactive drugs and by increasing venous blood flow through physical methods. However, anticoagulation cannot acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 44 publications
3
73
2
2
Order By: Relevance
“…In addition, Luther et al . recently confirmed that IFN‐γ delays thrombus neovascularization and resolution . IFN‐γ is an inflammatory cytokine produced by immune cells, and promotes inflammatory processes such as macrophage activation, and expression of chemokines and adhesion molecules involved in the recruitment of immune cells.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, Luther et al . recently confirmed that IFN‐γ delays thrombus neovascularization and resolution . IFN‐γ is an inflammatory cytokine produced by immune cells, and promotes inflammatory processes such as macrophage activation, and expression of chemokines and adhesion molecules involved in the recruitment of immune cells.…”
Section: Discussionmentioning
confidence: 91%
“…Nosaka et al showed that IFN-c delays thrombus resolution by inhibiting matrix metalloproteinase-9 production by monocytes, and Schonfelder et al demonstrated that absence of Tbet accelerates thrombus resolution by inhibiting interleukin-12 formation by monocytes [21,27]. In addition, Luther et al recently confirmed that IFN-c delays thrombus neovascularization and resolution [22]. IFN-c is an inflammatory cytokine produced by immune cells, and promotes inflammatory processes such as macrophage activation, and expression of chemokines and adhesion molecules involved in the recruitment of immune cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The cross‐talk of T cells with endothelium and coagulation proteins (such as thrombin) suggest a pivotal role of the immune system for coagulatory homoeostasis and the pathophysiology of venous thrombosis (Naldini et al , ; Carman & Martinelli, ). In contrast to the recently described role of T cells in thrombi (Luther et al , ), potential effects of DVT on systemic immune cell function have rarely been studied. Although recent observations indicate a link between venous thrombosis and changes in systemic immunity (Keragala et al , ), it remains unclear whether immune alterations are the cause or consequence of DVT and how they correlate with the severity of disease.…”
Section: Acute Deep Vein Thrombosis Systemic Inflammation and T Cellmentioning
confidence: 96%
“…But are NK cells really the only relevant source of IFN‐γ in DVT, as is implied by the NK cell depletion experiments of Bertin and coworkers? This aspect certainly needs further clarification, as in particular effector memory T‐cells were demonstrated to be crucial for the early inflammatory response in the same IVC ligation model and additional relevant sources of IFN‐γ could be involved . In addition to the NETosis‐related growth of inferior vena cava thrombi, at later stages T‐bet and IFN‐γ serve as critical elements in the resolution of IVC thrombi .…”
mentioning
confidence: 99%